The National Cryo-EM Facility at Frederick National Laboratory: Operational Procedures, Methods, and Outputs. (May 2020) - Baxa, Ulrich; Edwards, Thomas J.; Hutchison, Matt; Wier, Adam D.; Finney, Joseph; Wang, Helen; Subramaniam, Sriram
Abstract: Abstract : The National Cryo-Electron Microscopy Facility (NCEF) at the National Cancer Institute was launched in May of 2017 to provide free and rapid access to high-resolution cryo-EM data collection to United States researchers working on problems of broad general relevance to cancer biology. The decision about suitability of projects for data collection is made on a first-come, first-served basis by NCEF staff and is based solely on the quality of the screening images provided, without need for a scientific proposal. Here we provide an overview of the operation of the facility, typical data collection procedures, and some insights that have emerged from the structures reported from data collected at the facility.